Recent advances in capsule endoscopy: development of maneuverable capsules. (September 2012) - Keller, Jutta; Fibbe, Christiane; Rosien, Ulrich; Layer, Peter
One important disadvantage of modern capsule endoscopy is its lack of maneuverability. Thus, clinically available systems depend on transportation by spontaneous gastrointestinal motility. Even in subjects with normal motility, transit time for different intestinal segments may vary considerably, and relevant segments may be passed too quickly. This probably explains why approximately 10% of all pathologies are overlooked during small bowel investigations. Moreover, without maneuverable capsule endoscopes, the large inner surface of the stomach cannot be investigated properly. The most advanced approaches, which try to develop maneuverable systems for targeted inspection of the GI tract, use magnetic fields for steering of a videocapsule with magnetic inclusions. With such systems, preliminary clinical studies have already been performed. Other projects try to develop biologically inspired steering mechanisms such as capsules that can move on legs or they use electrical stimulation of the intestinal wall in order to induce contractions for propulsion of the videocapsule.